IoT-Based Home Automation System for Smart Living - Rashdan, Mostafa; Ahmad Almhaileej, Hoor Yaser; Almutairi, Shahad Ahmad; Eissa Ashkanani, Fatemah Khaled; Alhashimi, Amnah Hamad; Yousef Madoh, Reem Husain (International Conference on Bio-engineering for Smart Technologies (Online), 2025)
The proposed Home Automation System aims to integrate several household equipment and sensors to automate administration and monitoring for security purposes. This system uses IoT technology to improve home security, energy efficiency, and user comfort while remaining affordable and scalable at the same time. By designing a smart, robust, secure, and easy-to-use system, the user will be satisfied and innovated in terms of the recent technologies related to home automation. A prototype has been implemented, and tested. The final prototype incorporates several capabilities including remote monitoring, energy management, and customizable user interfaces. This makes smart home technologies easier to utilize.